To determine the effect of employee job satisfaction on employee motivation within the financial service sector of South Africa - Mouton, Esmarie (The IIE, 2020)
Employee job satisfaction and employee motivation are concepts that have been around for a long time. This study was aimed at uncovering the effect that employee satisfaction has on employee motivation within the financial service sector of South Africa, and to determine if there is a relationship between the two constructs. Variables that can have an effect on both employee job satisfaction and employee motivation was mentioned in this study. Variables that impact satisfaction are supervisor support and the balance between personal and work life. Variables of motivation include rewards, training and working conditions. A positive relationship between these two constructs could help organisations improve employee satisfaction which in turn improves motivation that has an effect on the overall success of an organisation. A quantitative research approach was used with a simple random sampling in order to give each employee a fair and even chance to be selected to participate. The employees of an organisation within the financial service sector was asked to complete an online questionnaire of which fifteen questionnaires were completed. Through the use of descriptive statistics and the Pearson Correlation Matrix the study concluded that there is a relationship between employee job satisfaction and employee motivation. This was shown by accepting (H0 and H1) and rejecting (H2) the relevant hypothesis. The study uncovered variables that could also have played a role in the results that should be further explored in future studies.
Keywords: Job satisfaction; Motivation; Financial services; Pearson Correlation Matrix